CDC42 role in APP-mediated cell migration - Pascoal, Flavia Sofia Rodrigues de Almeida (2018)
Cellular migration is transversal to several cellular processes such as embryogenesis, metastasis, immune response and regeneration. The amyloid precursor protein and the Cdc42 protein have been separately associated with several processes related to cell migration, namely: velocity, cell adhesion, cell polarization, and the development of migratory structures such as filopodia and lamellipodia. In this work we intended to confirm the role of APP in persistent direction of migration of neuronal-like cells, previously observed in our group, and to investigate if APP interacted with Cdc42 in this same process. Cell biology studies were carried out on SH-SY5Y cells transfected with APP-GFP and DsRed-Cdc42 (wt ou dominant negative, DN) cDNAs, and a Scratch Wound Healing assay was used to study cell migration parameters. Cells migration was monitored hourly for 13 hours by microscopy means, and the path, distance and velocity of the cells were analyzed with the help of the Image J software. We also analyzed the effects of these two proteins on the cell morphology using immunocytochemistry assays. Finally, we intended to study the influence of APP on the dynamics of F-actin in neuronal-like cells, to compare with our previous results in non-neuronal cells. For this we resorted to a FRAP analysis of live cells co-expressing APP-GFP and LifeAct-RFP, a fluorescent marker of F-actin. The results confirmed that APP positively influences persistence in the migration direction of SH-SY5Y cells. However, when co-expressed with Cdc42 wt the cells no longer migrated in a targeted manner. When Cdc42 was overexpressed but its catalytic activity inhibited (Cdc42 DN), the migration returned to a more directed pattern, which leads us to believe that APP does not increase persistence in the migration direction via Cdc42 activation. On the other hand, the presence of APP decreases both parameters of total migrated distance and the cells’ migration velocity in relation to the control GFP, and the presence of Cdc2 wt further decreased these values. In this case, inhibition of Cdc42 activity annulled APP effect, and cells returned to distance and velocity values similar to control cells. Regarding the acquisition of migratory phenotype, APP showed litle influence, unlike both Cdc42 (Wt and DN) that increased the percentage of cells with this phenotype, proving that the Cdc42 molecule alone is important for the cells polarization. Finally, we observed that APP tended to promote the dynamics of F-actin. These results contributed to better understand the mechanisms underlying the role of APP and Cdc42, and their functional interaction, in migration processes of neuronal-like cells.